Exercise therapy for the exercise naïve: The first step in obesity management - Sanjay Kalra; Anuradha Mandlekar; Nitin Kapoor (Journal of the Pakistan Medical Association, 2021)
Exercise is an integral part of obesity management and health promotion. This brief communication shares practical and pragmatic tips as to how to initiate physical activity in an exercise-naïve person with obesity. This information will be useful for all health care professionals who manage patients with obesity, including physicians and physiotherapists. A step-wise initiation of physical activity starting from flexibility training, balance practice and then aerobic and resistance exercises would help to provide a long term sustainable pattern of physical activity. Keywords: Exercise, Obese, Overweight, Obesity, Person-centered care, Physical activity, Workout.